Noninvasive Monitoring of Training Induced Muscle Adaptation with P31-MRS: Fibre Type Shifts Correlate with Metabolic Changes. (29th July 2013) - Hoff, Eike; Brechtel, Lars; Strube, Patrick; Konstanczak, Paul; Stoltenburg-Didinger, Gisela; Perka, Carsten; Putzier, Michael
Abstract : Purpose . To evaluate training induced metabolic changes noninvasively with P 31 magnetic resonance spectroscopy (P 31 -MRS) for measuring muscle fibre type adaptation. Methods . Eleven volunteers underwent a 24-week training, consisting of speed-strength, endurance, and detraining (each 8 weeks). Prior to and following each training period, needle biopsies and P 31 -MRS of the resting gastrocnemius muscle were performed. Fibre type distribution was analyzed histologically and tested for correlation with the ratios of high energy phosphates ([PCr]/[P i ], [PCr]/[ β ATP] and [PCr + P i ]/[ β ATP]). The correlation between the changes of the P 31 -MRS parameters during training and the resulting changes in fibre composition were also analysed. Results . We observed an increased type-II-fibre proportion after speed-strength and detraining. After endurance training the percentage of fast-twitch fibres was reduced. The progression of the [PCr]/[P i ]-ratio was similar to that of the fast-twitch fibres during the training. We found a correlation between the type-II-fibre proportion and [PCr]/[P i ] (r = 0.70, P < 0.01 ) or [PCr]/[ β ATP] (r = 0.69, P < 0.01 ); the correlations between its changes (delta) and the fibre-shift were significant as well (delta[PCr]/[P i ] r = 0.66, delta[PCr]/[ β ATP] r = 0.55, P < 0.01 ). Conclusion . Shifts in fibre type composition and high energy phosphate metabolite content covary in human gastrocnemius muscle. Therefore P 31 -MRS might be a feasible method for noninvasive monitoring of exercise-induced fibre type transformation.